The Development for Tourism Strategic Management Proposed Policy of Local Government Organization in Songkhla Lake Basin - ลาปีอี อัศว์ศิริ (Ratchaphruek Journal, 2019)
The objectives of this research were surveying to people opinion towards role for tourism management of local government organization in Songkhla Lake Basin and offering the guidance to the development for tourism strategic management policy. A questionnaire used as research tool to collect data by samples were 1,121 from 3 case studies. The data were analyzed by using frequency, mean, standard deviation and SWOT analysis. The results showed that the opinion in overall at the high level. In order to pursue these strategies of vision tourism was “Natural resources should be preserved, Development of communities and local at southern Gulf of Thailand by diversity of tourism management”. The suggestions were that the local government organization should be the innovators to improve the policy on responsibilities by encouraging from community including of the preventing and conserving the natural resources and environmental toward the master plan for Songkhla Lake Basin B. E. 2017-2036 that interchanges these strategies to the practical ways.